BRCA2 germline mutation carrier with five malignancies: a case report - Elena Su; Yann Christinat; Thomas McKee; Silvia Azzarello-Burri; Wolfram Jochum; Stefanie Fischer; Christian Rothermundt (Hereditary Cancer in Clinical Practice)
Abstract Background BRCA2 germline mutations are known to predispose carriers to various cancer types, including breast, ovarian, pancreatic and prostate cancer. An association with melanoma has also been reported. However, the full tumour spectrum associated with BRCA2 mutations, particularly in patients with other concurrent pathogenetic mutations, is unexplored. Case presentation We present a 70-year-old female patient with a pathogenic BRCA2 c.5946del variant. Over a period of 15 years, she has developed two independent breast cancers, well-differentiated liposarcoma, clear cell renal cell carcinoma and myeloproliferative neoplasia. This unusual tumour spectrum and the staggered occurrence of these tumours required multiple rounds of genetic testing and led to a delayed diagnosis of the BRCA2-associated tumour predisposition. In addition to the BRCA2 mutation, extended germline testing revealed an APC c.3920T > A variant and variants of unknown significance in the BRIP1 and ATR genes. The molecular analysis of the tumours revealed distinct profiles with differences in HRD status and in copy number variations, indicating no common origin. Conclusions Our case study revealed that the pathogenic BRCA2 c.5946del germline variant can be associated with an unusual tumour spectrum, which may lead to a delayed diagnosis of a hereditary tumour predisposition. Thus, upfront genetic testing using large multigene panels or whole-genome sequencing in encouraged, especially in cases with a prominent family history.